Roles of long noncoding RNAs in gastric cancer and their clinical applications - Sun, Weiliang; Yang, Yunben; Xu, Chunjing; Xie, Yi; Guo, Junming (Journal of cancer research and clinical oncology, 2016)
Purpose Gastric cancer ranks as the most common cancer in the world. However, the progresses of its diagnosis and treatment are still not satisfactory. The purpose of this study is to summarize the roles of lncRNAs associated with gastric cancer. Methods We searched lncRNAs associated with gastric cancer in PubMed. Results Long noncoding RNAs (lncRNAs), transcripts larger than 200 nucleotides, regulate gene expression at various levels. They are playing important roles in the occurrence and development of gastric cancer. They are involved in signaling pathways, crosstalk with microRNAs, and affecting metastasis by regulating epithelial-to-mesenchymal transition. By acting as oncogenes or tumor suppressors, lncRNAs contribute to gastric cancer occurrence and development. Several lncRNAs including HOTAIR, HULC, LINC00152, MALAT2, H19, GHET1, and GACAT3 have been demonstrated having oncogene activities, while other lncRNAs including LEIGC, GAS5, and FER1L4 have been thought as tumor suppressors. Conclusions Several lncRNAs from tissue, blood, and gastric juice have shown potential values in gastric cancer diagnosis or prognosis evaluation.